2001
DOI: 10.2334/josnusd.43.85
|View full text |Cite
|
Sign up to set email alerts
|

Histological and analytical studies of a tooth in a patient with cleidocranial dysostosis.

Abstract: A histopathological and analytical study of a permanent tooth from a patient with cleidocranial dysostosis (CCD) was performed. The patient was a 47-year-old woman, who had 10 erupted permanent teeth and 2 partially erupted and 19 completely impacted teeth, including supernumerary teeth. The erupted right upper premolar was extracted and observed using a light microscope and an electron probe X-ray microanalyzer (EPMA). Findings showed enamel hypoplasia, predominantly irregular globular dentin and Tomes' granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
3
14
0
1
Order By: Relevance
“…The formation of permanent teeth is normal with a delay of about 3–4 years. A disturbance of bone resorption along with an interposed fibrous tissue between the dental follicle and the mucosa or a lack of cellular cementum can be the cause of the unerupted teeth 23. Similar conspicuous absence of cellular cementum in the apical region was seen in the present case.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The formation of permanent teeth is normal with a delay of about 3–4 years. A disturbance of bone resorption along with an interposed fibrous tissue between the dental follicle and the mucosa or a lack of cellular cementum can be the cause of the unerupted teeth 23. Similar conspicuous absence of cellular cementum in the apical region was seen in the present case.…”
Section: Discussionsupporting
confidence: 82%
“…Similar conspicuous absence of cellular cementum in the apical region was seen in the present case. Along with it prominent areas of globular dentine were also noted as were also reported by Fukuta et al 23 These authors also observed enamel hypoplasia, predominant Tomes’ granular layer, obscure incremental lines of von Ebner and counter lines of Owen and lower quantities of calcium and phosphate in the enamel and dentine than those of the control sample. The associated bone in the present case showed irregular osteons suggestive of abnormal bone remodelling as has been put forth by Lukinmaa et al 24…”
Section: Discussionsupporting
confidence: 79%
“…Histological investigation of extracted permanent teeth in CCD show evidence of hypoplasia (90,91). Histological investigation of extracted permanent teeth in CCD show evidence of hypoplasia (90,91).…”
Section: Ameloblastsmentioning
confidence: 94%
“…Runx2 is involved in the early stages of enamel organ formation, and tooth morphogenesis and may also play a direct role in formation of tooth enamel. Histological investigation of extracted permanent teeth in CCD show evidence of hypoplasia (90,91). This does not appear to be the case for deciduous teeth (92).…”
Section: Ameloblastsmentioning
confidence: 99%
“…Delayed or arrested eruption has also been attributed to lack of cellular cementum. Less commonly alterations of hard dental tissues, eruption cysts, a high propensity for caries and narrow high palate have been found [23]. The most consistent dental findings in individuals with CCD are the presence of the second permanent molar with the primary dentition (80%), wide spacing in the lower incisor area, supernumerary tooth germs (70%), and parallel-sided ascending rami [20].…”
Section: Discussionmentioning
confidence: 99%